Triggers of change to public confidence in the police and criminal justice system: Findings from the Crime Survey for England and Wales panel experiment - Bradford, B; Myhill, A (SAGE Publications, 2015)
Accounts of public ‘trust and confidence’ in criminal justice agencies often fall into one of two camps. Instrumental accounts suggest that people trust police and the criminal justice system (CJS) when they believe them to be effective in fighting crime and reducing offending. Expressive or affective accounts, by contrast, suggest people place as much or more emphasis on the social meaning of justice institutions as on their instrumental activities. In this article we add to recent studies that have sought to weigh up the balance between instrumental and expressive factors. Using data from the Crime Survey for England and Wales panel experiment, we present evidence that trust in police and the wider CJS is implicated in public concerns about the nature of local order and cohesion. The expressive account appears to offer a better understanding of why people may grant trust to, or withdraw trust from, the police and the CJS.